Usulan Model Robust Newsvendor Problem Untuk Multi Produk dan Mempertimbangkan Permintaan Diskrit (Studi Kasus: Toko Roti X di Bandung) - Fran Setiawan; Paulina Kus Ariningsih; Stefanie Widya (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2018)
In Indonesia, the number of businesses that do not have a special building is 18.9 million business. One business that does not have a special building is a peddler. A considerable number of peddlers make the productivity and competitiveness of peddlers need to be improved. The problem faced by the peddler is to determine the type and the amount of each type of goods that must be brought each day. If the goods brought too many can cause overstocks that result in remaining goods can not be sold in the next sales period. If the goods brought too few can cause shortages that can lead to loss of opportunities to make sales or profit for a particular type of goods in a particular region. In this research, this problem will be modeled as a robust multi-product newsvendor problem with discrete demand. This model determines the optimal number that everyday peddler must bring for each type of product that maximizes the expected profit from the worst possibility that can occur when only some information from the demand distribution is known. After developing the model, then made a model completion program using Octave software. The case study used in this research is peddler of a bakery shop in Bandung. The results of the implementation of the developed model can increase the average of expected profit obtained by the first and second peddlers by 126.77% and 268.3987% respectively of the average current profit earned by the both peddlers.